2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--23118
|View full text |Cite
|
Sign up to set email alerts
|

The 360° of Information Fluency Delivery to Freshman Engineering Students

Abstract: Libraries since 2003. In this capacity she assists inventors throughout the state of West Virginia. She is also the bibliographer for Mechanical & Aerospace Engineering as well as for Civil & Environmental Engineering. Previously she worked as the head of the Physical Sciences Library and as an associate in the Government Documents department. She is a past president of the Patent & Trademark Resource Center Association. She holds a MLIS from the University of South Carolina, a MA from the University of Michig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These results exemplify assertions proposed in existing research. This course required students to examine the credibility of their sources across four major deliverables, indicating the impact of incorporating critical evaluation across different assignments [20] and making critical evaluation relevant to the students' engineering interests [19], [20]. Our results also exemplify the observation by Kajiwara, Taber, and Mullen [27] that teaching critical evaluation enables students to use a wide variety of non-traditional sources but evaluate them for reliability, giving them access to more types of useful and timely information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results exemplify assertions proposed in existing research. This course required students to examine the credibility of their sources across four major deliverables, indicating the impact of incorporating critical evaluation across different assignments [20] and making critical evaluation relevant to the students' engineering interests [19], [20]. Our results also exemplify the observation by Kajiwara, Taber, and Mullen [27] that teaching critical evaluation enables students to use a wide variety of non-traditional sources but evaluate them for reliability, giving them access to more types of useful and timely information.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature provides little guidance regarding which approaches to information-literacy instruction are most effective. Some studies suggest that library instruction is most effective when librarians partner with faculty members to make the information provided as pertinent to the students' area of study as possible [19], [20], [21]. Similarly, it has been suggested that embedded, co-curricular or "just-in-time" informationseeking instruction is superior to the traditional "one-shot" information session that typically takes place over an hour of class time, once per semester [20], [21], [22].…”
Section: Undergraduate Engineering Students and Information-seekingmentioning
confidence: 99%
See 2 more Smart Citations